(untitled) (The Proceedings of The International Conference on Climate Change, 2019)
Changing climate has significant impact on the river hydrology and water resources. An assessment of the availability of water resources in the context of future requirement and expected impact of climate change and its variability is critical for relevant national and regional long-term development strategies and sustainable development. Changes in the climate have been assessed through assessing the Metrologic parameters such as daily maximum and minimum temperature of the month, daily average temperature, annual rainfall, monthly rainfall of the monsoon season, and maximum daily rainfall of the year, number of rainy days in the year and number of rainy days in each month of monsoon season. It is observed that the 1) Maximum daily temperature shows increasing trend in summer season (March to June) and shows reducing trend in winter season (October to February) in the study area. This is indicative of extreme weather in climate change/advance scenario. 2) The monthly rainfall trend shows increasing trend for the magnitude of annual rainfall shows increasing trend in the study area. 3) The number of rainy days in the monsoon season (June to October) shows reducing trend. Rainfall-Runoff regression analysis has been carried out for base line and advance/climate change scenario to investigate the impact of climate change on Water Resources. This study will be helpful to water resources planners and decision makers regarding the strategies to be followed in view of changing climate.